2020
DOI: 10.7759/cureus.8238
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Right Ventricular Infarction in Inferior Wall Myocardial Infarction

Abstract: Background Ischemic heart disease, particularly inferior wall myocardial infarction (IWMI), is a significant issue in cardiac health. It can further add up to the morbidity and mortality when it is associated with right ventricular infarction (RVI). Elevated ST-segment elevations in the right chest lead number, three (V3R), and four (V4R), can be used to diagnose right ventricular infarction (RVI). The odds of RVI can be identified according to age groups, gender, and risk factors, including diabetes, hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…A recent study in Karachi Pakistan by Hassam et al reported a 36% prevalence of RVI in the setting of acute IWM which is a similar finding to our study result 12 . while in another study it was reported as 30%, which was less than our study result and study finding by Hassam et al 13 .…”
Section: Discussionsupporting
confidence: 92%
“…A recent study in Karachi Pakistan by Hassam et al reported a 36% prevalence of RVI in the setting of acute IWM which is a similar finding to our study result 12 . while in another study it was reported as 30%, which was less than our study result and study finding by Hassam et al 13 .…”
Section: Discussionsupporting
confidence: 92%
“…The relative infrequency of right ventricular involvement is attributed to the right ventricle's lower susceptibility to ischemia, owing to its smaller muscle mass and continuous coronary perfusion in both systole and diastole. 14 In a study conducted by Samin A et al, the occurrence of RVI in patients with acute inferior wall myocardial infarction was reported to be 27%, consistent with our www.pakheartjournal.com findings. Importantly, no statistically significant associations were observed between the incidence of RVI and the patients' gender or age, emphasizing the multifactorial nature of the factors influencing this cardiac complication.…”
Section: Discussionsupporting
confidence: 91%
“…2,4,5,7,8 The reported occurrence of RVI in IWMI spans a range of 27% to 48.5% in the existing literature. For instance, Ravikeerthy M and colleagues, 12 observed a 40% incidence, Memon AG and team, 13 found that among 198 cases with IWMI, 48.5% had evidence of RVMI, and Ali H et al 14 identified right ventricular involvement in 32% of 16 cases with IWMI. Therefore, our findings align with existing evidence regarding the incidence of RVMI in IWMI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that patients with inferior MI who are complicated by CAVB had an elevated risk of in-hospital events [ 10 , 11 ]. In one study, CAVB significantly influenced the outcome when associated with right ventricular infarction, leading to high mortality owing to cardiomyopathy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%